OP15 Long term outcomes and mortality among patients enrolled in a structured primary care-led diabetes programme. (2nd September 2017) - Riordan, F; McHugh, SM; Harkins, V; Kearney, PM
Abstract : Background: Limited data exists, internationally and in Ireland, on long-term outcomes among people with diabetes who are managed in primary care. The Midlands Diabetes Structured Care Programme encompasses evidence-based strategies to structure diabetes management within general practice: patient registration and recall, regular diabetes review visits, active role of the practice nurse in ongoing management, multidisciplinary specialist access, professional education, and remuneration. Our aim was to examine clinical outcome targets, complications and mortality among patients with diabetes enrolled in the programme since its establishment in 1998. Methods: Data were collected in 1999, 2003, 2008 and 2015, on outcomes (clinical parameters, complications and mortality) among patients with diabetes (≥18 years) registered with participating practices. Data were extracted from patient notes by clinical nurse specialists using a paper-based data collection form. Cause and date of death were obtained from national death records. Using Stata, chi-square tests were used to test differences in clinical outcomes over time. Cox proportional hazards regression was used to examine the association of baseline factors and mortality. Results: Patients from 1999 (n=376), were followed up in 2003 (n=229), 2008 (n=96) and 2016 (n=376).The proportion of patients with a recommended blood pressure target (<130/80 mmHg) increased from 9% in 1999 to 26% in 2016 (p<0.001), as did the proportion with a total cholesterol of <4.5 mmol/L (22% vs. 71%, p<0.001), and triglycerides<2.0 mmol/L (47% vs. 81%, p<0.001). The percentage achieving optimal glycaemic control (HbA1c≤7.0%) declined (52% vs. 34%). Between 1999–2016, 22% (n=81) of patients had ever experienced a macrovascular complication; primarily CVA (n=21, 6%), MI (n=16, 4%). In 1999, 18% (n=33) had retinopathy, increasing to 57% (n=59) by 2016. In total, 184 (49%) had died. Between 1999–2013 mortality was higher than background rates in the general population (SMR=2.2, 95% CI 1.9, 2.6). Only 25% (n=46) had cause of death recorded in their GP record. Where cause of death was obtained from national records (n=163), primary causes were MI (n=29, 17.8%) and pneumonia (n=23, 14%). Mean age at death was 77.7±9.3 years. Mortality was significantly higher among patients who were older at baseline. Gender, diabetes type, smoking status and clinical parameters at baseline were not significant predictors of mortality. Discussion: Improvements in the clinical profile of patients enrolled in the programme since its introduction suggests primary-care-led integrated diabetes management can perform favourably in the long-term. However, the high incidence of macrovascular complications, prevalence of retinopathy and mortality rate indicates the importance of effective management.